1999
DOI: 10.21273/hortsci.34.2.280
|View full text |Cite
|
Sign up to set email alerts
|

Drought Stress Increases Densities but Not Populations of Two-spotted Spider Mite on Buddleia davidii `Pink Delight'

Abstract: Two experiments were conducted to determine the effect of drought stress on the susceptibility of Buddleia davidii Franch. `Pink Delight' to the two-spotted spider mite (Tetranychus urticae Koch). In the first experiment, drought stress was imposed by withholding water until predawn xylem pressure potential fell below -1 MPa. Shoot growth was 75% less in drought-stressed than in nonstressed plants. Mite population densities were not affected, but no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…This pattern was also observed in Tetranychus urticae and Oligonychus pratensis on maize (Chandler et al, 1979), and in a mixed mite population of Tetranychus pacificus and Panonychus citri on almond (Youngman and Barnes, 1986;Youngman et al, 1988). Gillman et al (1999) observed that the damage caused by T. urticae increased on drought stressed buddleia plants. Ximénez-Embún et al (2016, 2017a, 2017b observed a global increase of performance of three important tomato mite pests, Tetranychus evansi, T. urticae and Aculops lycopersici, reared on drought-stressed tomato plants, especially for tomato-adapted strains in the case of T. urticae.…”
Section: Introductionsupporting
confidence: 59%
“…This pattern was also observed in Tetranychus urticae and Oligonychus pratensis on maize (Chandler et al, 1979), and in a mixed mite population of Tetranychus pacificus and Panonychus citri on almond (Youngman and Barnes, 1986;Youngman et al, 1988). Gillman et al (1999) observed that the damage caused by T. urticae increased on drought stressed buddleia plants. Ximénez-Embún et al (2016, 2017a, 2017b observed a global increase of performance of three important tomato mite pests, Tetranychus evansi, T. urticae and Aculops lycopersici, reared on drought-stressed tomato plants, especially for tomato-adapted strains in the case of T. urticae.…”
Section: Introductionsupporting
confidence: 59%
“…This pattern was also observed in Tetranychus urticae and Oligonychus pratensis on maize (Chandler et al, 1979), and in a mixed mite population of Tetranychus pacificus and Panonychus citri on almond (Youngman and Barnes, 1986; Youngman et al, 1988). Gillman et al (1999) observed that the damage caused by T. urticae increased on drought stressed buddleia plants. Ximénez-Embún et al (2016, 2017a, 2017b) observed a global increase of performance of three important tomato mite pests, Tetranychus evansi, T. urticae and Aculops lycopersici , reared on drought-stressed tomato plants, especially for tomato-adapted strains in the case of T. urticae .…”
Section: Introductionmentioning
confidence: 98%